1991
DOI: 10.1002/smj.4250120704
|View full text |Cite
|
Sign up to set email alerts
|

The performance impact of strategy ‐ manager coalignment: An empirical examination

Abstract: This paper develops a theoretical model that explains the impact of the fit between top executive characteristics and strategic orientation on organizational performance. Using the Miles and Snow typology as an integrative framework, the central propositions of the model were evaluated. The results of the empirical examination provided significant support for the administrative dimension, an aspect of the typology that has been largely overlooked thus far. Further, it was found that firms achieving a greater d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
275
5
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 373 publications
(296 citation statements)
references
References 64 publications
11
275
5
5
Order By: Relevance
“…Such characteristics include (1) chairs with both political connections, which helps to rule out any conflicting effects of two different types of political connections; (2) age, measured in year; (3) gender, which equals 1 if a chair is male; (4) educational attainment, which is coded as 6 for doctorate degree, 5 for master's degree, 4 for undergraduate degree, 3 for high school, 2 for middle school, 1 for primary school, and 0 for those below primary school (Thomas et al 1991); and (5) tenure, measured by the years in the position. We also used duality of chair and CEO to measure whether the position of chair and chief executive officer (CEO) were held by the same person, to proxy executive power (Sauerwald et al 2016).…”
Section: Control Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such characteristics include (1) chairs with both political connections, which helps to rule out any conflicting effects of two different types of political connections; (2) age, measured in year; (3) gender, which equals 1 if a chair is male; (4) educational attainment, which is coded as 6 for doctorate degree, 5 for master's degree, 4 for undergraduate degree, 3 for high school, 2 for middle school, 1 for primary school, and 0 for those below primary school (Thomas et al 1991); and (5) tenure, measured by the years in the position. We also used duality of chair and CEO to measure whether the position of chair and chief executive officer (CEO) were held by the same person, to proxy executive power (Sauerwald et al 2016).…”
Section: Control Variablesmentioning
confidence: 99%
“…In addition, top executives with different functional backgrounds have different strategic priorities (e.g., Hambrick and Mason 1984), and those with sales or marketing background may develop a different strategic perception of charitable giving. We coded chair has sales/marketing background using the position and department affiliation of the executive's longest working experience (Thomas et al 1991).…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firms led by CEOs who were younger, had more wealth invested in company stock, and had previous experiences in marketing, R&D and/or engineering also showed greater R&D spending. Similarly, Thomas, Litschert, and Ramaswamy (1991) found, using a sample in the computer industry, that firms following market innovation strategies were likely to be led by younger and more educated CEOs. More recently, Lin, Lin, Song and Li (2011) found that CEOs' educational level, political connections, and performance-driven compensation all predicted greater levels of R&D spending in the context of manufacturing firms in China.…”
Section: Ceo Humility and Firm Randd Spendingmentioning
confidence: 89%
“…Previous studies have found CEO age to be related to lower levels of innovation (e.g., Barker & Mueller, 2002;Thomas et al, 1991), and CEO age is traditionally included in models predicting firm performance (e.g., Chatterjee & Hambrick, 2007;Olsen et al, 2013). CEO tenure was omitted in final regressions since it was not significant in any of the models.…”
Section: Control Variablesmentioning
confidence: 99%